2014
DOI: 10.1002/oby.20793
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel lncRNA in gluteal adipose tissue and evidence for its positive effect on preadipocyte differentiation

Abstract: ContextPeripheral lower body fat is associated with lower cardiometabolic risk. Physiological differences in gluteal compared to abdominal subcutaneous (sc) adipocyte functions are known but the molecular basis for depot differences in adipocyte function is poorly understood.ObjectiveTo identify novel gene regulatory pathways that underlie the heterogeneity of human fat distribution.Design and methodsAbdominal and gluteal adipose tissue aspirates obtained from 35 subjects (age=30±1.6 years; BMI=27.3±1.3kg/m2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 15 publications
10
83
1
Order By: Relevance
“…In addition, lncRNAs tend to be expressed at lower levels compared with mRNAs [2931], and a high proportion of lncRNAs are preferentially expressed in specific tissues or cell lines [30, 32]. The expression of adipose lncRNAs is low and depot-specific [33, 34]. According to its position with respect to protein coding genes, a lncRNA can be classified into one or more of five categories [21]: sense, antisense, bidirectional, intronic, and intergenic (Fig.…”
Section: Lncrnasmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, lncRNAs tend to be expressed at lower levels compared with mRNAs [2931], and a high proportion of lncRNAs are preferentially expressed in specific tissues or cell lines [30, 32]. The expression of adipose lncRNAs is low and depot-specific [33, 34]. According to its position with respect to protein coding genes, a lncRNA can be classified into one or more of five categories [21]: sense, antisense, bidirectional, intronic, and intergenic (Fig.…”
Section: Lncrnasmentioning
confidence: 99%
“…Recently, a study has shown that HOTAIR participated in human subcutaneous preadipocyte differentiation [34]. HOTAIR was expressed in human gluteal fat but not in abdominal subcutaneous adipose tissue, and HOTAIR expression increased by twofold during gluteal preadipocyte differentiation in vitro [34].…”
Section: Lncrnas In White Adipogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have suggested that lncRNAs serve as important controllers during adipogenesis [6], adipocyte differentiation [7], liver development [8], and hepatic lipid metabolism [9]. Some lncRNAs play an important role in the cholesterol metabolism in HepG2 cells [10].…”
Section: Introductionmentioning
confidence: 99%